Family - micro ecclesia - Brînzea, Nicolae; Silivestru, George-Ștefan (Technium Social Sciences Journal, 2022)
The family is a divine part of God's plan. It is the fundamental element of a strong society. Marriage is not only a model of interhuman existence, it is the model of man's relationship with God. Marriage is the mystery of sanctifying love. The family is recognized as the "little Church" or the "Home Church", the mission of both parents being a prophetic one in the sense of understanding the universal priesthood of each active member of the Church of Christ. The family is also the environment where the child naturally learns to pray. It is the first and fundamental school of moral and social life, a community of love. The great mystery of the family is the mystery of transfiguration, of spiritualized love, which lifts man up to God.